Nadzorować i kształtować. Wymiary społeczeństwa sieciowego - Baranowski, Mariusz; Luczys, Piotr (Człowiek i Społeczeństwo, 2015)
The purpose of this article is to show the different possibilities of applying supervision in the network society, which seems to be particularly susceptible to these types of practices. The scope and forms of social control in the dimension of the network will be discussed at both the level of individual applications of the generally available tools, as well as at the more sophisticated system of specialized programs. Apart from the perspective of surveillance in terms of advanced technology, the possible defensive tendencies also will be presented.